Evaluasi Kualitas Spermatozoa Ayam Brahma, Cochin dan Bangkok Sebagai Dasar Penerapan Teknologi Inseminasi Buatan pada Ayam Kampung - Asnawi Asnawi; Budi Indarsih; Dewi Haryani; Sukartha Jaya; Maya Nachida; Adji Santoso Dradjat (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Research on the evaluation of the spermatozoa quality of Brahma, Cochin and Bangkok chickens as the basis for the application of artificial insemination technology in native chickens has been carried out. The purpose of this study was to evaluate the spermatozoa quality of Brahma, Cochin and Bangkok rooster as the basis for determining the spermatozoa dose for artificial insemination in local chickens. method research was used a completely randomized design (CRD) with three treatments, that is: Brahma, Cochin and Bangkok rooster. Each treatment was repeated five times. Cement storage is carried out by inserting an artificial vagina into the cloaca of the rooster and stimulating it to climb the hen. The collected sperm were analyzed at the Animal Reproduction Laboratory, Faculty of Animal Science, Mataram University. The variables observed included motility, viability and morphology of spermatozoa. The results of studied that the spermatozoa motility of Brahma, Chicin and Bangkok rooster were 72 ± 2.74%. 74 ± 2.24% and 73 ± 2.74% (P> 0.05) respectively; The spermatozoan viability of Brahma rooster and Bangkok rooster was 99.2 ± 1.30%, 99.4 ± 0.55% and 99.2 ± 1.10% (P>0.05)respectively. The spermatozoan morphology of brahma rooster, chicin rooster and Bangkok rooster was 94.6 ± 2.30%, 94.4 ± 2.70% and 97.4 ± 2.07% (P> 0.05), respectively. Cochin rooster and Bangkok rooster respectively, 62.6 ± 7.92 x 107, 57 ± 5.83 x107 , and 65.2 ± 12.28 x107, respectively. The results of the study concluded that Brahma, Cochin and Bangkok rooster had good sperm quality and could be able to used in artificial insemination of Kampung hens.